Comparative evaluation of two peripheral information systems using motion sickness subjective rating - Mustaffa, Norrizal; Karjanto, Juffrizal; Md. Yusof, Nidzamuddin; Terken, Jacques; Frank, Delbressine; Matthias, Rauterberg (2020)
Motion sickness (MS) mitigation devices have gained attention in the research related to automated vehicle (AV) driving. While different modalities have been proposed, the visual-related modality has shown promises as most activities inside the AV. In this study, we measured the level of MS experienced by the 38 participants using two visual-based prototypes when they underwent the automated driving test rides. Results indicated that participants experienced less MS when using P1 than P2.